Comparison of outcome between laparoscopic inguinal hernia repair and open inguinal hernia repair - Vallipriya, V.; Surendran, S. (International Surgery Journal, 2022)
Background: Laparoscopic and open surgery techniques have been explored, and each technique has its advantages and pitfalls. Therefore, this study intended to carefully evaluate and compare the outcome of operative duration, post-operative pain, post-operative analgesic requirement, and post-operative complications between laparoscopic inguinal hernia repair and open incisional inguinal hernia repair surgery. Methods: In this comparative study, patients were divided into 2 groups, 25 patients underwent laparoscopic inguinal hernia repair, and 25 patients underwent open inguinal hernia repair. Visual analog scale (VAS), post operative analgesic requirement and complications were analyzed between groups. Results: The mean age of open surgery patients was 43.12±12.51, while it was 44.67±18.22 in the laparoscopic group. Forty-five of the cases presented with unilateral hernia, of which 28 showed right laterality and 17 displayed left laterality. In 05 cases, bilateral representation was observed. The average duration of open inguinal hernia repair was 54.23±9.41 minutes, while laparoscopic took 68.94±12.35 minutes, which was statistically significant (p<0.0001). The post-operative pain in VAS just after and post 6, 12 and 24 hours were significantly lower with laparoscopic surgery. Seroma was the most commonly noted post-operative complication, especially in laparoscopic casesy. Conclusions: The study found that the laparoscopic inguinal hernia repair technique was statistically superior to the open incision method in reducing post-operative pain and analgesic requirements. However laparoscopic method had a longer surgery duration as compared to the open surgery procedure.